PALESTINE : A FOUR THOUSAND YEAR HISTORY - Masalha, Nur (I.B. Tauris, 2022)
This rich and magisterial work traces Palestine's millennia-old heritage, uncovering cultures and societies of astounding depth and complexity that stretch back to the very beginnings of recorded history. Starting with the earliest references in Egyptian and Assyrian texts, Nur Masalha explores how Palestine and its Palestinian identity have evolved over thousands of years, from the Bronze Age to the present day. Drawing on a rich body of sources and the latest archaeological evidence, Masalha shows how Palestine's multicultural past has been distorted and mythologised by Biblical lore and the Israel–Palestinian conflict. In the process, Masalha reveals that the concept of Palestine, contrary to accepted belief, is not a modern invention or one constructed in opposition to Israel, but rooted firmly in ancient past. Palestine represents the authoritative account of the country's history